Catch-Up Growth and Discontinuation of Fludrocortisone Treatment in Aldosterone Synthase Deficiency - Tosun, Busra Gurpinar; Demirkol, Yasemin Kendir; Menevse, Tuba Seven; Kaygusuz, Sare Betul; Ozbek, Mehmet Nuri; Altincik, Selda Ayca; Guran, Tulay (Endocrine Society, 2022)
Background Aldosterone synthase deficiency (ASD) caused by mutations in the CYP11B2 gene is characterized by isolated mineralocorticoid deficiency. Data are scarce regarding clinical and biochemical outcomes of the disease in the follow-up. Objective Assessment of the growth and steroid profiles of patients with ASD at the time of diagnosis and after discontinuation of treatment. Design and method Children with clinical diagnosis of ASD were included in a multicenter study. Growth and treatment characteristics were recorded. Plasma adrenal steroids were measured using liquid chromatography-mass spectrometry. Genetic diagnosis was confirmed by CYP11B2 gene sequencing and in silico analyses. Results Sixteen patients from 12 families were included (8 females; median age at presentation: 3.1 months, range: 0.4 to 8.1). The most common symptom was poor weight gain (56.3%). Median age of onset of fludrocortisone treatment was 3.6 months (range: 0.9 to 8.3). Catch-up growth was achieved at median 2 months (range: 0.5 to 14.5) after treatment. Fludrocortisone could be stopped in 5 patients at a median age of 6.0 years (range: 2.2 to 7.6). Plasma steroid profiles revealed reduced aldosterone synthase activity both at diagnosis and after discontinuation of treatment compared to age-matched controls. We identified 6 novel (p.Y195H, c.1200 + 1G > A, p.F130L, p.E198del, c.1122-18G > A, p.I339_E343del) and 4 previously described CYP11B2 variants. The most common variant (40%) was p.T185I. Conclusions Fludrocortisone treatment is associated with a rapid catch-up growth and control of electrolyte imbalances in ASD. Decreased mineralocorticoid requirement over time can be explained by the development of physiological adaptation mechanisms rather than improved aldosterone synthase activity. As complete biochemical remission cannot be achieved, a long-term surveillance of these patients is required.
Demircioglu, Serap/0000-0002-5172-5402; Guran, Tulay/0000-0003-2658-6866; Yesiltepe Mutlu, Gül/0000-0003-3919-7763; , Sare Betul/0000-0001-8457-8042; Bayramoğlu, Elvan/0000-0002-6732-8823; Gurpinar Tosun, Busra/0000-0002-7588-9807; Bereket, Abdullah/0000-0002-6584-9043
Keywords: Aldosterone Synthase Deficiency; Hypoaldosteronism; Catch-Up Growth; Steroid Hormone Profile; Follow-Up; Children